THE ROLE OF EARLY CHILDHOOD TUTORS IN OPTIMIZING THE EARLY CHILDHOOD LEARNING ENVIRONMENT AT PAUD NOOR RAKHMAH BANDUNG - Ria Maryana (IKIP Siliwangi Bandung, 2018)
Abstract Non-formal Early Childhood is a symbol of the council school, when viewed from the tuition fee that is voluntary and not mandatory, so do not imagine this school has the good facilities. In terms of places, early childhood doesn't have own building, mostly using village hall or other public facilities such as mosques or musholla. This limitation also has an impact on early childhood space for learning. Children cannot play and move freely and develop themselves. The environmental of learning should be a lot of attention, the environment will affect the learning process and learning outcomes of children . This research is qualitative research with study descriptive. This research is based on the problem of various conditions of environmental management learning at Early Chilhood Education (PAUD) Noor Rakhmah related to facilities and infrastructure. Tutors have an important role in optimizing the management of early childhood learning environments. The purpose of this research is to obtain data that is: (1) The planning process conducted by Tutor PAUD Noor Rakhmah in optimizing the early childhood learning environment. (2) The implementation process conducted by Tutor PAUD Noor Rakhmah in optimizing the early childhood learning environment. (3) The evaluation process conducted by PAUD Noor Rakhmah Tutor on the utilization of early childhood learning environment.Keywords: Environmental Management Learning, Early Childhood